A STUDY ON THE IMPACT OF INNOVATIVE HR PRACTICES ON EMPLOYEE PRODUCTIVITY AMONG WOMEN EMPLOYEES IN IT INDUSTRY WITH REFERENCE TO BANGALORE CITY - Fernandes, Ms. Sharmila; Bhatt, Ms. Himresha; Kumar V, Dr Santhosh (The journal of contemporary issues in business and government, 2022)
Information technology is not only one of India’s fastest-growing businesses, but also a major factor in propelling the country’s economy and changing its reputation from that of a developing economy to that of a global powerhouse. The retention of skilled personnel has become more important as the market has become increasingly competitive and human resource managers have faced a serious scarcity of quality specialists. This is crucial as it assures the sustainability and productivity of the firm. Despite the fact that "staff poaching" is all the rage in the business world, even a little slip-up might result in the loss of brilliant minds to a rival company. According to the literature, there are two types of employee turnover: functional and dysfunctional. Dysfunctional turnover occurs when a top performer departs the company, whereas functional turnover occurs when an unproductive employee leaves. Since dysfunctional turnover is a major issue for HR managers, it is the subject of this research. When an employee departs, it takes another seven weeks to fill their role, which has a negative impact on the team’s output. Staff retention has received far less attention than employee turnover in previous studies. The purpose of this investigation is to specify the connection between creative HR practises and productivity in the workplace. The researcher looks at the several ways that independent and dependent variables are defined. For the study, researchers handed 400 professionally-designed questionnaires to female workers at 20 software firms in Bangalore City. New methods of human resource management were shown to have a significant detrimental effect on productivity.